Examination of Influential Factors Shaping Savings Culture among Selected First-Year UoT Students in South Africa - Msomi, Thabiso Sthembiso; Cloete, Melanie Bernice (Journal of Ecohumanism, 2025)
Economies in the global South, especially in Southern Africa, are dealing with high unemployment, persistent inequality, and slow economic growth. This makes a strong savings culture vital for economic progress. South Africa, in particular, is facing the dual challenges of low savings rates and poor financial literacy, especially among its youth. This study delves into the factors that shape the savings habits of first-year university students in South Africa. By understanding their financial behaviour’s, we can develop targeted interventions to promote a healthy savings culture. Using an explanatory research approach and a quantitative design, data were gathered from a representative sample of 103 first-year accounting students at a South African university through a survey questionnaire. coefficients of the regression model showed a strong link between students’ saving behaviour and key factors like saving culture, financial education, and personal values & financial discipline. In contrast, income level showed a weak correlation, indicating that ingrained saving habits, financial knowledge, and personal values are more crucial in shaping students’ saving habits. These findings offer valuable insights for policymakers and educators aiming to develop effective strategies to enhance financial literacy and build a stronger savings culture among young adults in South Africa, ultimately contributing to the region’s long-term economic well-being.